All About Love - Knauss, Stefanie (My University, 2015)
Pedro Almodóvar’s reappropriations of religious concepts and motifs (especially of Catholicism) frequently provide the focal point for his critique of both the religious establishment and gender norms grounded in religion and reinforced in society. Tracing Almodóvar’s critical and transformative representation of the central Christian concept of love in his cinema, in particular through the analysis of three films “about love”, Law of Desire, Live Flesh, and Volver, this paper shows that the materialization of this concept in Almodóvar’s oeuvre goes beyond the citation of preconceived ideas, and represents the emergence of a new vision of love, potentially transformative of individuals and societies.
The Materialization of a Foundational Concept of Christianity in Pedro Almodóvar’s Queer Cinema
Keywords: Liebe; Begehren; Queer; Christentum; Film; 791 Öffentliche Darbietungen, Film, Rundfunk; Kino; Pedro Almodóvar; Das Gesetz der Begierde; Live Flesh - Mit Haut und Haar; Volver - Zurückkehren